Nilai Didaktis Dalam Dongeng Anak Jepang (Analisis Dongeng Tsuru No Ongaeshi) - Unsriana, Linda (Lingua Cultura, 2007)
The article has purpose to see the didactic value in fairy tale. The didactic value can be given to children through the character in the fairy tale by identifying the character act or behaviour. Data library shows that fairy tale can be used as one of tools for value and moral education. The data were used to support the research that fairy tale also can be used for on dan ongaeshi value. In the end, it can be concluded that fairy tale was effective tools to give value education to the children because it did not forced the children to accpet it. Â Â